2019
DOI: 10.1021/acs.analchem.8b04393
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Screening of Tamoxifen Abundance and Effect Using Mass Spectrometry and Raman-Spectroscopy

Abstract: Monitoring drug uptake, its metabolism, and response on the single-cell level is invaluable for sustaining drug discovery efforts. In this study, we show the possibility of accessing the information about the aforementioned processes at the single-cell level by monitoring the anticancer drug tamoxifen using live single-cell mass spectrometry (LSC−MS) and Raman spectroscopy. First, we explored whether Raman spectroscopy could be used as a label-free and nondestructive screening technique to identify and predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…However, it is complicated to quantify the drug uptake or metabolism response at a single cell level using the RM alone. Recently, it has been demonstrated that correlating the Raman signal with the destructive mass spectrometry analysis renders the drug and metabolite quantification at a single-cell level possible [ 62 ]. Indeed, the combined platform is capable of providing more information about drug uptake, metabolism, and effects at the single-cell level, demonstrating the potential to investigate pharmacokinetics at the single-cell level.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is complicated to quantify the drug uptake or metabolism response at a single cell level using the RM alone. Recently, it has been demonstrated that correlating the Raman signal with the destructive mass spectrometry analysis renders the drug and metabolite quantification at a single-cell level possible [ 62 ]. Indeed, the combined platform is capable of providing more information about drug uptake, metabolism, and effects at the single-cell level, demonstrating the potential to investigate pharmacokinetics at the single-cell level.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, due to recent increasing interest in combining datasets from imaging modalities 19 , it may also be of interest to study the systematic variations between Raman signals and mass spectrometry results (as well as other omics methods) by using integrative computational approaches. Interestingly, we have already found several weak but significant linear correlations between the intensities of Raman peaks identified by VIP scores and the abundance of tamoxifen or its metabolite at the single-cell level as identified by MS 4 . This data may suggest a metabolic relationship between MS profiles and Raman spectra and the possibility to predict these values.…”
Section: Discussionmentioning
confidence: 85%
“…Minimize the laser intensity at the sample to ~2.4 mW/µm 2 so that cells survive laser exposure. 4. Set up the microchamber at 5% CO 2 and 37 °C.…”
Section: Raman Spectral Imaging and Spectral Processingmentioning
confidence: 99%
See 2 more Smart Citations